WHITE MATTER HYPERINTENSITIES AND GAIT IMPAIRMENT AMONG OLDER ADULTS WITH AND WITHOUT COGNITIVE IMPAIRMENT. (16th November 2018) - Sakurai, R; Inagaki, H; Tokumaru, A; Sakurai, K; Kitamura, A; Watanabe, Y; Shinkai, S; Awata, S
Abstract: Background: Gait impairment reflects subtle cognitive impairment (CI). Although gait impairment has been associated with white-matter hyperintensity (WMH) severity, cognitive-related differences of the association are not fully understood. This study examined the association between WMH and gait performance among older adults with and without CI. Methods: Gait performance and WMH were assessed in 150 community-dwelling older adults comprising 53 with CI [Mini-Mental State Examination (MMSE) < 24, mean age = 78.7 years] and 97 without CI (MMSE > 23, mean age = 78.9 years). Gait velocity was calculated at steady state on a five-meter pathway. Gait variability was assessed as stride time and stride length variabilities with a five-meter electronic walkway. The volume in WMH was derived by automated segmentation, using a 1.5 T magnetic resonance imaging. Results: Adjusted multiple logistic regression analyses showed that greater WMH was associated with slower gait velocity, and greater stride time and stride length variabilities among older adults with CI. In older adults without CI, only stride length variability was associated with WMH. Adjusting for gait velocity, the significant association of WMH and gait variability was attenuated in older adults with CI whereas the association in older adults without CI remained significant. Conclusions: Our results indicate that gait variability, but not gait velocity, is vulnerable to WMH severity in older adults regardless of having cognitive impairment. We also found cognitive-dependent differences in the association between WMH and gait, which may suggest the trajectory of cognitive decline among older adults with greater WMH burden.